PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI MELALUI DISPLIN KERJA DI DINAS PENDIDIKAN KABUPATEN BOJONEGORO (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
The purpose of this study was to determine and analyze the influence of leadership and work environment on work discipline. To find out and analyze the influence of leadership, work environment and work discipline on employee performance. To find out and analyze the influence of leadership and work environment on employee performance through work discipline. This research is an explanatory research and has a quantitative approach. The population in this study were 90 people. The number of samples used in as many as 90 people. The technique used in this sampling is total sampling. Data analysis and processing were carried out using path analysis. Based on the results of the analysis, it can be concluded that there is a significant influence between Leadership and Work Environment on Work Discipline at the Bojonegoro Regency Education Office. There is a significant influence between leadership and work discipline on employee performance. There is no significant influence between the Work Environment and Employee Performance. There is a significant influence between Leadership on Employee Performance through Work Discipline. There is no significant influence between the Work Environment on Employee Performance through the Work Discipline.